John Olsen's Full Stroke at 70 m of His Leg of the Gold Medal 4 x 100 m Freestyle Relay at the 1998 Perth World Championships - Rushall, B. S.
Video pictures (12 frames) and the appropriate technical/ biomechanical explanations for John Olsen's Full Stroke at 70 m of His Leg of the Gold Medal 4 x 100 m Freestyle Relay at the 1998 Perth World Championships. John Olsen exhibits an uneven stroke. The timing and movement sequences of both arms are different. While the left arm exhibits a desirable elbow-up position, the right arm does not. The long downward press of the right arm would cause a drop in the swimmer's momentum due to an inertial lag. That delay would consume energy more inefficiently. In the middle of the pull of both arms the elbow moves faster than the hand suggesting a diminution in propulsive power due to a letting-go and change in the angle of the propulsive surface. The head position could be improved. Its forward-looking position does produce a slight body angle for part of the stroke resulting in increased frontal resistance.